ONE STOP CENTRE INFORMATION FOR TOURISTS AT RURAL AREA, SG SIPUT, PERAK - Madzir, Intan Haniza (IRC, 2020)
This project has conducted a deep research on preparing an online platform for the native people at Sg Siput, Perak to promote the places and activities that may be an attraction for the tourists outside the village area. This effort is to help the native people to widen their source of income and increase their economy by promoting the uniqueness of their village. The hope for this project is to acknowledge the people that they should experience new culture and try something new by visiting places in rural area and engage them with the native people.